Microbial influencers and cotton leaf curl disease (CLCuD) susceptibility: a network perspective - Aqueel, Rhea; Badar, Ayesha; Ijaz, Umer Zeeshan; Malik, Kauser Abdulla (Frontiers in Microbiology, 2024)
Biotic stresses such as plant viruses e.g. Cotton Leaf Curl Virus can alter root-associated and leafassociated microbial diversity in plants. There are complex ecological dynamics at play with each microbe contributing to multitude of biotic and abiotic interactions thus deciding the stability of the plant's ecosystem in response to disease. Deciphering these networks of interactions is a challenging task. The inferential research in microbiome is also at a nascent stage, often constrained by the underlying analytical assumptions as well as the limitations with respect to the depth of sequencing. There is also no real consensus on which network-wide statistics to identify the influential microbial players in a network. Guided by latest developments in network science, particularly, recently published metrics such as Integrated View of Influence (IVI), and some other centrality measures, in this study, we provide an exposé of the most influential nodes in the rhizospheric and phyllospheric microbial networks of the Cotton Leaf Curl Disease (CLCuD) susceptible, partially tolerant, and resistant cotton varieties. It is evident from our results that the CLCuD resistant Gossypium arboreum possesses an equal share of keystone species which helps it in withstanding ecological pressures. In the resistant variety, the phyllosphere harbors the most influential nodes whereas in the susceptible variety they are present in the rhizosphere. Based on hubness score, spreading score and IVI, the top 10 occurring keystone species in FDH-228 (resistant) variety were Actinokineospora, Cohnella, Thermobacillus, Clostridium, Desulfofarcimen, and MDD-D21. Elusimicrobia, Clostridium-sensu-stricto_12, Candidatus woesebacteria, and Dyella were identified as the most influential nodes in PFV-1 (partially tolerant) variety. In the PFV-2 (susceptible) variety, the keystone species were identified as Georginia, Nesterenkonia, Elusimicrobia Acetivibrio, Tepedisphaerales, Chelatococcus, Nitrosospira, This concept deciphers the diseased and healthy plant's response to viral disease which may be microbially mediated.